A British university case study of the transitional experiences of student-athletes. (November 2015) - Brown, Daniel J.; Fletcher, David; Henry, Ian; Borrie, Andy; Emmett, Jo; Buzza, Alan; Wombwell, Simon
Abstract: Objectives: Within Great Britain, increasing numbers of elite sport performers are attending higher education institutions. The current study presents an exploration of the transitional experiences of these individuals at a specific British university. Wylleman and Lavallee's (2004) developmental model on transitions faced by athletes and Stambulova's (1997, 2003) athletic career transition model were used to provide the theoretical foundation of inquiry. Design and method: An instrumental case study design was adopted to provide an in-depth analysis of student-athletes' experiences at a university. The case university was selected based on its provision of elite sport support services. To acquire a holistic understanding, interviews were conducted with current and recently graduated student-athletes from the university, and focus groups were run with university staff (viz. administrators, coaches, and support staff). Qualitative data were analyzed using a thematic framework approach. Results: Elite student-athletes at the British university were found to experience simultaneous athletic, academic, psychological, and psychosocial transitions. To overcome the transitional demands, student-athletes were found to draw on a variety of internal (e.g., self-awareness) and external (e.g., academic flexibility) resources and to implement coping strategies (e.g., seeking social support). Potential barriers to successful transitions were also identified (e.g., parental overprotection). Conclusions: These findings advance the limited existing literature on British university student-athletes' transitional experiences and suggestions are provided for how other universities can enhance provision for their elite student-athletes. Highlights: Explores transitional experiences of student-athletes at a British university. Considers simultaneous athletic, academic/vocational, psychological, and psychosocial transitions. Discusses related transitional demands, resources, barriers, and coping strategies. Identifies unique support provision compared to other British universities.